Regulated cell death in sepsis-associated liver injury: molecular mechanisms and therapeutic implications - Zou, Kun; Wang, Na; Wang, Linyu; Zhu, Zhongqiang; Gu, Mengyuan; Zhang, Junqiang (Frontiers in Immunology, 2026)
Sepsis-associated liver injury (SALI) is a critical determinant of sepsis prognosis, characterized by extensive hepatocellular death and dysregulated immune responses. Emerging evidence highlights the pivotal role of regulated cell death (RCD) — including apoptosis, necroptosis, pyroptosis, and ferroptosis — in driving hepatic dysfunction and systemic inflammation. These cell death modalities, once considered distinct, are now recognized as components of an interconnected network that integrates inflammatory, metabolic, and oxidative signals within the liver’s unique immunometabolic microenvironment. This review systematically summarizes the molecular mechanisms of major RCD pathways implicated in SALI, and elucidates their crosstalk and convergence through shared mediators such as caspase-8, the NLRP3 inflammasome, lipid peroxidation, and liver-specific metabolic regulators including bile acid signaling. We further discuss key signaling cascades including PI3K/Akt, Nrf2, and NF-κB that orchestrate RCD execution and inflammatory amplification in SALI. By integrating mechanistic insights with emerging translational perspectives, this review highlights RCD as a unifying framework for understanding liver injury and identifying therapeutic entry points to restore hepatic and systemic homeostasis during sepsis.